First Record of Lenomyrmex inusitatus (Formicidae: Myrmicinae) in Ecuador and Description of the Queen - T. Delsinne; F. Fernández (Psyche: A Journal of Entomology)
The rarely collected ant Lenomyrmex inusitatus Fernández 2001 is recorded for the first time in Ecuador. The queen is described. The new record is the southernmost limit of distribution for the genus. A key to the workers of the six Lenomyrmex species and a key for the known queens are provided.